Pembrolizumab plus Lenvatinib in patients with metastatic Renal Cell Carcinoma: real-world evidences from the international ARON- 1 study - Porta, Camillo; Massari, Francesco; Taha, Tarek; Grande, Enrique; Bourlon de los Ríos, María Teresa; Kanesvaran, Ravindran; Basso, Umberto; Molina-Cerrillo, Javier; Alonso-Gordoa, Teresa; Myint, Zin W.; Fornarini, Giuseppe; Buttner, Thomas; et al. (Springer Science and Business Media LLC, 2025)
Background: Pembrolizumab plus lenvatinib is a treatment option for metastatic Renal Cell Carcinoma (mRCC). In the ARON-1 study we investigated we the real-world experiences gained from the use of this combination for mRCC. Methods: We retrospectively investigated real-world clinical outcomes of mRCC patients receiving pembrolizumab plus lenvatinib within the ARON-1 study. Overall survival (OS) was calculated from the start of pembrolizumab plus lenvatinib to death for any cause. Progression-Free Survival (PFS) was defined as the time from the start of pembrolizumab to progression or death from any cause. Duration of response (DoR) was defined as the time from the start of pembrolizumab to disease progression or death, whichever occurred first, in patients who achieved complete remission (CR) or partial response (PR). Overall Response Rate (ORR) was defined as the proportion of patients who achieve a CR or PR per RECIST criteria. Adverse events were retrospectively collected from electronic and paper charts and categorized by the Common Terminology Criteria for Adverse Events (CTCAE) v5.0. Results: Overall, we included 202 mRCC patients treated with pembrolizumab plus lenvatinib. The median follow-up time was 15.1 months. The median OS was not reached (NR), with a median PFS of 25.6 months and an Overall Response Rate (ORR) of 59%. The median Duration of Response (DoR) was 26.2 months. G3-G4 adverse events (AEs) were observed in 92 patients (46%), with hypertension being the most common AE (13%). Conclusions: Pembrolizumab plus lenvatinib is an effective and tolerable treatment for mRCC also in the real-world setting. ©The authors ©Springer Science and Business.
Keywords: ARON- 1; Immune-combinations; Lenvatinib; Pembrolizumab; Real-world data; Renal cell carcinoma; Survival